The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.4103/ijn.ijn_345_21
|View full text |Cite
|
Sign up to set email alerts
|

Renal lymphoma diagnosed on kidney biopsy presenting as acute kidney injury

Abstract: Introduction: Renal manifestations associated with hematolymphoid malignancies are known. Primary or secondary involvement of the kidney by lymphomatous infiltration has various clinical presentations. Acute kidney injury is not an uncommon finding in relation to lymphomatous interstitial infiltration proven on kidney biopsy. However, diagnosing it solely on renal biopsy remains a challenge and needs expertise and aid of immunohistochemistry as the prognosis is dismal. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
0
0
Order By: Relevance
“…Acute kidney injury (AKI) incited by direct cell infiltration is uncommon (10,11). Nie et al and Nuguri et al each reported only one patient with CLL/SLL and kidney injury due to associated infiltrates in recently published retrospective cohort studies of patients with lymphoproliferative disorders (12,13). AKI as the first indication that prompts the diagnosis of CLL/SLL is extremely rare, with only seven reported cases in the literature (14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute kidney injury (AKI) incited by direct cell infiltration is uncommon (10,11). Nie et al and Nuguri et al each reported only one patient with CLL/SLL and kidney injury due to associated infiltrates in recently published retrospective cohort studies of patients with lymphoproliferative disorders (12,13). AKI as the first indication that prompts the diagnosis of CLL/SLL is extremely rare, with only seven reported cases in the literature (14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…A second serum immunofixation 2 months later showed biclonal IgG kappa and lambda. Immunoglobulin levels were measured with a total IgA of 1.05 g/l [0.7-4], IgM of 0.18 g/l [0.4 2.3], and IgG of 8.83 g/l(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Quantification of the…”
mentioning
confidence: 99%